;tldr
Without loss of generality we can assume the circles have Radius R and are centered on the $x$ axis at $(\pm p, 0)$, $a$ is semi-major axis, $b$ is semi-minor axis and $\sqrt{a^2-b^2}=\pm c$ is where the foci are on the x-axis. $A$ is area.
$$b^2 = \frac{4R^2+p^2\sqrt{1+8R^2/p^2}-p^2}{4}\approx 2R^2$$
$$a^2= \frac{5p^2+4R^2+3p^2\sqrt{1+8R^2/p^2}}{4} \approx 2(p^2+2R^2 ) $$
$$c^2=\frac{6p^2+2p^2\sqrt{1+8R^2/p^2}}{4} \approx 2(p^2+R^2)$$
$$A=\pi ab \approx 2\pi R\sqrt{p^2+2R^2}$$
Let circle be $(x-p)^2+y^2=R^2$ and the ellipse be $\frac{x^2}{a^2}+\frac{y^2}{b^2}=1$.
Solve for $y$ in terms of $x$. Requiring the discriminant of the resulting quadratic in $x$ to be $0$ establishes a condition for the circle being tangent to the ellipse:
$$\frac{p^2}{c^2}+\frac{R^2}{b^2}=1$$
Where $a^2=b^2+c^2$. $a$ is the semi-major axis, $b$ is the semi-minor, and $c$ is the distance of the focus from the center.
Minimizing the squared area of the ellipse will minimize the Area of the ellipse so :
$$A^2 = \pi^2 a^2b^2$$
The tangency condition suggests we parmeterise with:
$$c^2=p^2\sec^2\theta$$
$$b^2=R^2\csc^2 \theta$$
So :
$$A^2/(\pi^2R^2)=(p^2\sec^2\theta + R^2\csc^2\theta)csc^2\theta$$
So:
$0= (2p^2\sec^2\theta \tan\theta - 2R^2\csc^2\theta \cot\theta)\csc^2\theta-2(p^2\sec^2\theta + R^2 \csc^2\theta)\csc^2\theta\cot\theta$
$(p^2\sec^2\theta + R^2 \csc^2\theta) \cot \theta= (p^2\sec^2\theta \tan \theta - R^2\csc^2\theta\cot \theta)$
$2R^2\csc^2\theta \cot\theta = p^2\sec^2\theta(\tan \theta - \cot \theta)$
$2R^2 \cot \theta = p^2 \tan^2\theta (\tan \theta - \cot \theta)$
$2R^2=p^2\tan^2 \theta (\tan^2\theta -1)$
$p^2\tan^4 \theta - p^2\tan^2\theta -2R^2=0$
$$\tan^2\theta = \frac{p + \sqrt{p^2+8R^2}}{2p}$$
Where we only take the plus sign since $\tan ^2 \theta \ge 0$ and it's assumed the radius is non-zero.
$\sec^2\theta = \frac{3p + \sqrt{p^2+8R^2}}{2p}$
$\cos^2\theta = \frac{2p}{3p + \sqrt{p^2+8R^2}}$
$\sin ^2 \theta = \frac{p +\sqrt{p^2+8R^2}}{3p + \sqrt{p^2+8R^2}}$
$\csc^2\theta = \frac{3p + \sqrt{p^2+8R^2}}{p +\sqrt{p^2+8R^2}}=1+ \frac{2p}{p +\sqrt{p^2+8R^2}}$
$$c^2 = \frac{6p^2 + 2p^2\sqrt{1+8R^2/p^2}}{4}$$
$$b^2=\frac{3R^2 + R^2\sqrt{1+8R^2/p^2}}{1 +\sqrt{1+8R^2/p^2}}=R^2+ \frac{2R^2}{1 +\sqrt{1+8R^2/p^2}}=\frac{R^2(\sqrt{1+8R^2/p^2}+3)}{\sqrt{1+8R^2/p^2}+1}$$
$$b^2 = \frac{4R^2+p^2\sqrt{1+8R^2/p^2}-p^2}{4}\approx 2R^2$$
$$a^2= \frac{5p^2+4R^2+3p^2\sqrt{1+8R^2/p^2}}{4} \approx 2(p^2+2R^2 ) $$
$A\approx 2\pi R\sqrt{p^2+2R^2} $
To minimize $a$:
$$a^2=(p^2\sec^2\theta + R^2\csc^2\theta) $$
$p^2 \tan^4 \theta = R^2 $
$\tan^2\theta = R/p$
$\sec^2\theta = (p+R)/p$
$\csc^2\theta = (p+R)/R$
$$a=p+R$$
$$b^2= R(p+R)=aR$$
$$c^2=p(p+R)=ap$$